Individual variability of cerebral autoregulation, posterior cerebral circulation and white matter hyperintensity. (9th February 2016) - Liu, Jie; Tseng, Benjamin Y.; Khan, Muhammad Ayaz; Tarumi, Takashi; Hill, Candace; Mirshams, Niki; Hodics, Timea M.; Hynan, Linda S.; Zhang, Rong
Abstract : Key points: Cerebral autoregulation (CA) is a key mechanism to protect brain perfusion in the face of changes in arterial blood pressure, but little is known about individual variability of CA and its relationship to the presence of brain white matter hyperintensity (WMH) in older adults, a type of white matter lesion related to cerebral small vessel disease (SVD). This study demonstrated the presence of large individual variability of CA in healthy older adults during vasoactive drug‐induced changes in arterial pressure assessed at the internal carotid and vertebral arteries. We also observed, unexpectedly, that it was the 'over‐' rather than the 'less‐reactive' CA measured at the vertebral artery that was associated with WMH severity. These findings challenge the traditional concept of CA and suggest that the presence of cerebral SVD, manifested as WMH, is associated with posterior brain hypoperfusion during acute increase in arterial pressure. Abstract: This study measured the individual variability of static cerebral autoregulation (CA) and determined its associations with brain white matter hyperintensity (WMH) in older adults. Twenty‐seven healthy older adults (13 females, 66 ± 6 years) underwent assessment of CA during steady‐state changes in mean arterial pressure (MAP) induced by intravenous infusion of sodium nitroprusside (SNP) and phenylephrine. Cerebral blood flow (CBF) was measured using colour‐coded duplex ultrasonography at the internal carotid (ICA) and vertebral arteries (VA). CA was quantified by a linear regression slope (CA slope) between percentage changes in cerebrovascular resistance (CVR = MAP/CBF) and MAP relative to baseline values. Periventricular and deep WMH volumes were measured with T2‐weighted magnetic resonance imaging. MAP was reduced by −11 ± 7% during SNP, and increased by 21 ± 8% during phenylephrine infusion. CA demonstrated large individual variability with the CA slopes ranging from 0.37 to 2.20 at the ICA and from 0.17 to 3.18 at the VA; no differences in CA were found between the ICA and VA. CA slopes measured at the VA had positive correlations with the total and periventricular WMH volume ( r  = 0.55 and 0.59, P  < 0.01). Collectively, these findings demonstrated the presence of large individual variability of CA in older adults, and that, when measured in the posterior cerebral circulation, it is the higher rather than lower CA reactivity that is associated with WMH severity. Key points: Cerebral autoregulation (CA) is a key mechanism to protect brain perfusion in the face of changes in arterial blood pressure, but little is known about individual variability of CA and its relationship to the presence of brain white matter hyperintensity (WMH) in older adults, a type of white matter lesion related to cerebral small vessel disease (SVD). This study demonstrated the presence of large individual variability of CA in healthy older adults during vasoactive drug‐induced changes in arterial pressure assessed at the internal carotid and vertebral arteries. We also observed, unexpectedly, that it was the 'over‐' rather than the 'less‐reactive' CA measured at the vertebral artery that was associated with WMH severity. These findings challenge the traditional concept of CA and suggest that the presence of cerebral SVD, manifested as WMH, is associated with posterior brain hypoperfusion during acute increase in arterial pressure.